Alliteration Concept And its Representions in Calligraphic Configerations - Khudair Abbas Dalli, Assi.Prof. Dr (lark, 2022)
The current research sheds light on the research problem, which is ((what is alliteration concept and its representations in calligraphy configurations?)), where the study aimed to reveal alliteration concept and its representations in calligraphy configurations, within the limits of spatial research in the Arab and Islamic countries for the period from 2000 to 2021, and the chapter The second, it included two sections, the first (alliteration between meaning and structures) and the second topic (the foundations of alliteration in building calligraphy  composition), while the third chapter was the research community and amounted to (40) Samples and (Four) The research samples were selected intentionally and at a rate of 10%. As for the fourth chapter, the results of the research were the most important of them: 1. The text is a means of interrogating the text and reviving its semantic campaign and re-forming it according to limited foundations and concepts in line with the self-vision of the calligrapher. The researcher suggested conducting complementary studies for (Alliteration concept and its representations in the rest of the decorative formations
Keywords: Alliteration- Representations- Calligraphy Configurations